The Technique Features of the 1990s Prose Poem in Iraq: The Technique Features of the 1990s Prose Poem in Iraq (Journal of the College of Education for Women, 2019)
Abstract:The prose poem of the 1990s is considered one of the importantcontributions of the Iraqi poetic scene. The poem found a position in the Iraqipoetry because of the favor of a group of youth poets who lefty clear traces.Their linguistic techniques often violate the domain o9f language, significanceand image.The poems of those youth poets moved the verse towards reality todrink from its abundant springs in order to stand on a rigid ground. Theirlinguistic traces are characterized by paradox and astonishment that are usedby the poet to construct his poem.The paradox was considered an ideal means for constructing apoem by some of them. The poem moved towards definitions and thesedefinitions gave the poem strength to break the horizon of writing for thelisteners.From another side, the poets of the 1990s were gown wearing thegown of the old through the spread of wisdom in the poem, while they wereyouth. Furthermore, the pot included some of the philosophic views which donot go out of the subject of philosophy and searching for reality through thesubject of life and death. More details are given in this study.